Integrated Grasshopper Algorithm-Evolutionary Programming Technique for Distributed Energy Resources Allocation - Kamalrolzaman M.A.; Musirin I.; Mansor M.H.; Salimin R.H.; Ismail N.L.; Mohamed Kamari N.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer programming; Distributed computer systems; Electric power transmission; Electric power transmission networks; Energy resources; Evolutionary algorithms; Optimal systems; Distributed energy resource; Distributed Energy Resources; Distributed generation installation; Evolutionary programming techniques; Fitness; Objective functions; Optimisations; Optimization techniques; Power system networks; Resources allocation; Installation